Liquid Metal Nanodroplets: Light‐Induced Shape Morphing of Liquid Metal Nanodroplets Enabled by Polydopamine Coating (Small 9/2019). Issue 9 (1st March 2019) - Gan, Tiansheng; Shang, Wenhui; Handschuh‐Wang, Stephan; Zhou, Xuechang
Abstract : In article number1804838, Xuechang Zhou and co‐workers design a shape morphing nanosystem by encapsulating liquid metal (LM) nanodroplets with polydopamine (PDA). Under near‐infrared light irradiation, the PDA shell converts light energy into heat energy and locally heats the LM core, which triggers the shape transformation of the LM core from a spherical shape to ellipsoid.